Dampak Local-based Entrepreneurship terhadap Aset Penghidupan yang Berkelanjutan: Studi Kasus Wisata Lembah Mbencirang, Mojokerto - Yuni Setyaningsih; Tony Hanoraga (JURNAL SOSIAL HUMANIORA (JSH), 2022)
Tourism is one of the most effective tools for economic development. According to Haryana, 4.5% of Indonesia's total GDP was significantly contributed to by tourism in 2018. The World Economic Forum ranked Indonesia 40th in the Travel and Tourism Competitiveness Index (TTCI) out of 140 countries in 2019. Nonetheless, this contribution decreased significantly during the covid-19 pandemic outbreak in 2020. Mursalin et. al. argued that the tourism industry was hardest hit by the pandemic's impact on economic growth. Understanding this phenomenon, it became intriguing to investigate the gradual tourism revival and livelihood assets of local tourism-based enterprise in Wisata Lembah Mbencirang by the Village Owned Enterprises (BUMDES). This study's objectives included identifying and analyzing the core problematization and livelihood assets of locally based entrepreneurship, as well as its community impact. This study was conducted in Kebontunggul Village, Mojokerto, East Java. This study employed a variety of methods. Several analytical tools, including pentagon assets and sustainable livelihood assets, were utilized. The results demonstrated that local entrepreneurship had both positive and negative effects on communities. The vulnerability context that shook people's livelihoods must be overcome by bolstering social and human capitals to maintain resilience, as well as the government's commitment to enhancing policies pertaining to locally-based entrepreneurship. In conceiving and ensuring sustainability, the community implemented a variety of livelihood strategies through adaptation. When feasible, livelihood adaptation would continue, and incomes would increase.